Wastewater Electrolysis for Hydrogen Production - Cartaxo, Marco (2022)
Due to its highest gravimetric energy density, H2 has been regarded as the preferred clean-energy carrier, with potentially environmentally-friendly production through the solar-assisted WS. Since human activities generate enormous amounts of WW, H2 production from this new resource has gained attention as an emergent technology. This paper addresses the most relevant and current aspects of H2 production from WWEL, and electricity generation from RES. In this sense, the state of art of H2 production, especially from WS, is presented here, as well as the main approaches to electricity generation from RES, with the greatest potential for viability. A new approach on this matter, which is part of the work that is being developed by the authors of this study, was also herein presented.